ARCO AÓRTICO DIREITO ASSOCIADO A DIVERTÍCULO DE KOMMERELL DE ARTÉRIA SUBCLÁVIA ESQUERDA ABERRANTE - Catarino, Joana (2019)
Introduction: Right sided aortic arch is a rare condition and half of the cases are associated with an aberrant left subclavian artery that can become aneurysmal (Kommerell´s diverticulum). Fewer than 50 cases have been reported in literature and a number of operative strategies are described. The authors report a case of a right aortic arch with Kommerell diverticulum of the aberrant left subclavian artery corrected through a hybrid approach. Clinical case: The patient was a 51-year-old female with a prior history of hypertension, cervical herniated disc requiring surgery and hysterectomy. The angio CT showed a right aortic arch with a 30 mm Kommerell diverticulum, with mild esophageal compression but no associated symptoms. The patient was referred to surgical treatment through a hybrid approach. The intra and post operatory period were without any complication and patient was discharged 3 days later. Conclusion: An endovascular hybrid approach may significantly reduce the morbidity and mortality of the repair of these aneurysms and, if effective and durable, could become an important surgical strategy for these patients. However, long term outcomes of such therapy are not yet established so, cautious follow up is needed.